(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Endoscopic sinus surgery has emerged as a mainstay in the surgical management of chronic sinus disease and nasal polyps. A prospective study of 60 patients who underwent endoscopic sinus surgery was undertaken at the department of Ear Nose Throat Head and Neck Surgery, Fatimah Jinnah Medical College /Sir Ganga Ram Hospital, Lahore, during the period of Jan 2012- March 2014. All patients underwent detailed history and examination including CT scans. Following parameters were studied indications for surgery, post operative complications and follow up outcomes.